Implementation Of Internet Of Things (IOT) In Air Quality Monitoring (AQI) - Ahmad Fikri; Mohammad Ridwan; Dine Agustine (Lembaga Pengembangan Kinerja Dosen, 2025)
This research implements an Internet of Things (IoT) based air quality monitoring system using fuzzy logic to provide real-time, accurate, and easily accessible information. The system integrates various gas sensors (MQ-7, MQ-135, MQ-131) and a particle sensor (Sharp GP2Y1010AU0F) connected to an ESP32 microcontroller. Collected air quality data, including CO, NO₂, O₃, and PM2.5 concentrations, is sent to a server and processed using a fuzzy inference system to generate an Air Quality Index (AQI) and its corresponding status. The data is then visualized on a web-based dashboard developed with CodeIgniter, featuring real-time graphs and tables, and also provides automated WhatsApp notifications to alert users about current air quality conditions. System testing confirms the accuracy and consistency of sensor readings, the proper functioning of the fuzzy logic processing, and the reliability of data transmission and notification features. This system offers an efficient solution for monitoring air quality, enhancing environmental awareness, and supporting preventive measures in the campus environment of Universitas Islam Syekh Yusuf and the wider community.